2019
DOI: 10.47963/toe.v13i.296
|View full text |Cite
|
Sign up to set email alerts
|

Curriculum Planning Activities of Heads of Schools and Academic Performance of Senior High School Students in the Northern Region of Ghana

Abstract: The study examined the effects of curriculum planning activities of heads of senior high schools on students’ academic performance in Ghana. The cross-sectional survey design was used in the study. The sample size was 445. The proportionate stratified random and purposive sampling techniques. Data were collected using questionnaire, interviews and focus group discussions. Analysis of data involved the use of binary logistic regression, cross-tabulation and thematic analysis. It was found that of the eight pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Instructional approaches that demand students' active participation in task accomplishment is absent in the Ghanaian classroom (Azure, 2015). The traditional, teachercentered, lecture method is still used in teaching biological concepts by majority of the teachers at the second cycle schools in Ghana (Amadu, 2018). This approach to teaching places the focus on the teacher, forces students to adopt a passive role in their own learning (Garret, 2008) and is not particularly as effective, compared to the alternative student-centred approaches, of improving (Precious, & Feyisetan, 2020).…”
Section: Problem Statementmentioning
confidence: 99%
“…Instructional approaches that demand students' active participation in task accomplishment is absent in the Ghanaian classroom (Azure, 2015). The traditional, teachercentered, lecture method is still used in teaching biological concepts by majority of the teachers at the second cycle schools in Ghana (Amadu, 2018). This approach to teaching places the focus on the teacher, forces students to adopt a passive role in their own learning (Garret, 2008) and is not particularly as effective, compared to the alternative student-centred approaches, of improving (Precious, & Feyisetan, 2020).…”
Section: Problem Statementmentioning
confidence: 99%
“…However, as Gyang (1979, as cited in Abroampa et al, 2020 observed, this method made many students hate mathematics. The paper noted that school mathematics was characterized by punishment, force, and fear, which forced some students to end their schooling prematurely (Abudu & Mensah, 2016;Mereku, 2019).…”
Section: Introductionmentioning
confidence: 99%